Insights from a Regional-Level Study of Traditional Plant-Based Treatments for Kidney and Urinary Disorders in Lebanon - Beyrouthy, Marc; Bou Saba, Jimmy; Al Kazzi, Mariline; Sadaka, Carmen; Tokajian, Sima; Al Samra, Lynn; Sinno, Aia; Fares, Sara; Kandil, Caren; Al Khoury, Charbel (Ethnobiology and Conservation, 2025)
Kidney and urinary disorders are globally prevalent conditions with significant health and socio-economic impacts, often requiring comprehensive and culturally adapted healthcare approaches. In Lebanon, numerous plant species are utilized in ethnopharmacological practices for treating renal and urinary ailments. This study aimed to systematically document and analyze the traditional use of plants in Lebanese communities for kidney and urinary disorders, focusing on specific plant parts, origins, preparation methods, and regional variations. Data were collected over nine years from 310 informants across 26 districts, resulting in the identification of 289 plant species from 73 families. Using the Consensus and Fidelity Level for Ethnobotanical Studies (CONCEFS) guidelines, we employed the Relative Frequency of Citation (RFC), Use Value (UV), and Relative Importance Index (RI) metrics to assess each plant’s cultural significance and medicinal versatility. The findings indicate structured usage patterns, with high RFC scores for plant parts like aerial parts and roots and preparation methods such as decoction and infusion. Indigenous and cultivated plant species exhibited the highest RFC scores, underscoring a reliance on local resources. The Chi-Square Test of Independence confirmed significant non-random associations between plant characteristics and medical conditions, reflecting culturally embedded preferences and practical efficacy. This research highlights the depth of traditional knowledge in Lebanese communities, offering insights into region-specific practices that could inform future pharmacological studies and conservation efforts. By bridging traditional practices with modern medicine, this study underscores the potential for integrating culturally relevant treatments into contemporary healthcare for kidney and urinary disorders.